Perceptions and attitudes concerning individuals with disabilities in ancient Greece: physical exercise as a means of prevention and treatment of health-related problems - Iordanis Stavrianos; Vasilios Kaimakamis; Vasilios Tsimaras; Athanasios Anastasiou (Exercise and Quality of Life)
In the history of human kind in all ethnic groups and communities there have been individuals with physical or mental disabilities. Until the 18th century not only these individuals did not receive any support or care by their community but they were rather treated as inferior with a diminishing way. More or less the same attitude occurs to the ancient Greek world, where old age, limited psychomotor skills and potential disability were perceived as evidence of deprivation of the grace of gods. A minor acknowledgment of individuals with disabilities started from Athens, since there were several benefits introduced on behalf of the disabled for the very first time in the history of human kind. In the ancient times Greeks made use of physical exercise as a mean for therapeutic as well as prevention purposes against various diseases. Thus, a great number of distinguished physicians such as Herodikos and his student Hippocrates recommended physical exercise as the ideal treatment of several health-related problems.